DEVELOPMENT STAGES OF E-COMMERCE IN SINGAPORE AND UZBEKISTAN - Kudratova Feruza Nasriddinovna; Zakirova Sayyora Alimovna (TADQIQOTLAR.UZ, 2024)
Abstract: This study explores the development stages of e-commerce in Singapore and Uzbekistan, providing a comparative analysis of their respective journeys in building digital economies. Singapore's e-commerce evolution is marked by early investments in digital infrastructure, comprehensive regulatory frameworks such as the Electronic Transactions Act and the Personal Data Protection Act, and continuous innovation in cybersecurity and intellectual property protection. This strategic approach has positioned Singapore as a global e-commerce leader. Conversely, Uzbekistan is in the nascent stages of e-commerce development, focusing on expanding digital infrastructure and internet access. The country faces challenges due to an underdeveloped legal framework, with specific needs for robust data protection, cybersecurity measures, and clear e-commerce regulations. This study highlights the key milestones and current status of e-commerce in both countries, offering insights into how Uzbekistan can leverage Singapore’s successful model to accelerate its e-commerce growth and integration into the global digital economy.